LabVIEW를 이용한 소형 유도전동기의 권선고장 자동진단 - 宋明現(Myung-Hyun Song); 朴奎南(Kyu-Nam Park); 韓東奇(Dong-Gi Han); 禹奕在(Hyeok-Jae Woo) (전기학회 논문지 P권, 55(4), 2006)
In this paper, an auto detection method of stator winding fault of small induction motor is suggested. The Park's vector pattern which is obtained from 3-phase current signal by d-q transforming, is very good to detect winding fault. Comparing the Park's vector pattern of testing motor with its of healthy motor, the Park's vector pattern of fault motor is became an ellipse and the asymmetry is increased by the winding fault series. So for detecting the dis-symmetry, id-filtered function, Min-value, and Max-value are suggested for auto detecting. Using LabVIEW programing, 3-phase healthy motor and several kind of winding fault motors are tested and the test results are shown that the suggested method can gives us a possibility of an auto detecting winding fault.